ISSUES OF ENTREPRENEURSHIP DEVELOPMENT IN NATIONAL LEGISLATION - Inomov Asrorbek Axrorjon oʻgʻli (Modern American Journals, 2025)
In this article, the role of national legislation in the development of entrepreneurship, the results of the current laws in practice, and ways to solve current problems are covered in detail.
Keywords: Entrepreneurship, legislation, economic reforms, private property, investments, digitalization, public policy, economic liberalization, innovations.